P108 Healthcare Professionals Perceptions of Self Management in COPD – Important, Challenging and Misunderstood. (19th November 2012) - Young, HML; Harrison, S; Apps, LD; Warrington, VL; Singh, SJ
Abstract : Introduction: There is increasing focus on the importance of self management (SM) within COPD. Literature from other chronic diseases highlights the challenges of implementing SM and the lack of specialist training available. Currently we have no knowledge of what Health Care Professionals (HCP) understand by the term 'SM' and their perceptions of the challenges to successfully supporting SM strategies specifically with a COPD population. A greater awareness of HCP understanding and beliefs surrounding SM is likely to inform training, enhance professional development and improve delivery of SM to patients with COPD. Aim: To explore HCP understanding of SM and their perceptions of the challenges of supporting COPD patients with SM in order to identify education, training and resource needs. Method: A purposive sample of 14 respiratory HCP participated in semi-structured interviews. Interviews were transcribed verbatim and thematic analysis was performed. Two experienced researchers (SH, LA) analysed a sub-group of interviews to enhance rigour. Results: Three main themes emerged from the data: 1. Understanding of SM – meaning, importance . 2. Supporting SM – advising and working in partnership. 3. Challenges to delivering SM - service, cultural and perceived patient barriers. Conclusion: HCP demonstrate a lack of understanding regarding SM which subsequently impacts upon its successful delivery. In spite of this, all HCP agreed that SM is an important aspect of care for COPD patients. HCP feel apt in the delivery of advice and many worked in partnership with their patients but most failed to consistently address additional SM needs. HCP could improve their delivery of individualised SM by abandoning preconceptions about their patients and enhancing skills to assist patients with core SM strategies including: problem solving, decision making and taking action. Addressing service challenges such as lack of time, prioritisation of achieving QOF indicators and increasing workload demands, as well as the cultural challenges created by professional hierarchies may allow HCP to deliver quality SM more consistently and effectively.